Waveguide-Based Photonic Sensors: From Devices to Robust Systems - Milvich, Johannes (Karlsruhe Series in Photonics & Communications, 2022)
Integrated photonic sensor systems are miniaturized, mass-producible devices that leverage the mature semiconductor fabrication technology and a well-established ecosystem for photonic circuits. This book aims at a holistic treatment of waveguide-based photonic sensor systems by analyzing photonic waveguide design, photonic circuit design and readout design. Across all levels, a special emphasis is given to system-level performance optimization under realistic environmental conditions.